The Relationship Burnout With The Performance of Implementing Nurses in The Inpatient Room at Rawa Lumbu Hospital 2019 - deniati, kiki (STIKes Medistra Indonesia, 2020)
Burnout is physically and emotionally exhausted and as a change in attitude or behavior. As a result of exhausted or the saturation of the work it self can appear in the form of reduced job satisfaction, low productivity and deteriorating performance. Nursing performance are activities provided to clients through the implementation of nursing care to achieve the goal of health care. This study aims to determine whether the relationship burnout with the performance of implementing nurses in the inpatient room at Rawa Lumbu Hospital 2019. This research method using observational analytic design with cross sectional approach. The population in this study were all nurses in inpatient room at Rawa Lumbu Hospital totaling 30 nurses, once incorporated into the formula slovin number of samples as many as 28 nurses. The results of the research were in the statistical test Chi-Square was obtained p value of 0.028 can be inferred p value (0.028) < value α (0.05), it indicates that there is a relationship burnout with the performance of nurses in the inpatient room at Rawa Lumbu Hospital 2019. The conclusion is Burnout can affect the performance of the nurse, when nurses feel any fatigue or burnout (burnout) it is no longer the situation becomes conducive working environment if this situation is allowed to drag, it can cause performance degradation.